2005
DOI: 10.1063/1.2133931
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic capture of a single magnetic nanoparticle using nanoelectromagnets

Abstract: We demonstrate the fabrication of nanoelectromagnets and the magnetic capture of a single magnetic nanoparticle. The magnetic nanoparticles are extracted from magnetotactic bacteria and their diameter is approximately 50 nm. We show that a single nanoparticle is captured at each corner of the serpentine-shaped nanoelectromagnet, and the maximum magnetic field of 35 mT ͑and the maximum magnetic-field gradient of 4 ϫ 10 5 T/m͒ is shown to be created at the capture spots of the nanoelectromagnet. It is also shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…[1] In biological applications, nanometer scale electromagnets can also manipulate magnetic particles. [2,3] In this paper, we demonstrate a Faraday's induction experiment using a nanometer scale electromagnet with two concentric rings. The nano-transformer shows linear induction responses with a large mutual inductance value and this linear characteristic suggests a possibility of magnetic sensor applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In biological applications, nanometer scale electromagnets can also manipulate magnetic particles. [2,3] In this paper, we demonstrate a Faraday's induction experiment using a nanometer scale electromagnet with two concentric rings. The nano-transformer shows linear induction responses with a large mutual inductance value and this linear characteristic suggests a possibility of magnetic sensor applications.…”
Section: Introductionmentioning
confidence: 99%
“…As the SEM images of the experimented CNT indicated that the diameter of the catalyst was 50 nm, the magnetic momentum of the 50 nm Fe nanoparticle ( m = ∼6 × 10 −17 A m 2 ) was used [26]. The magnetic force between the Ni pattern and the Fe catalyst was simulated by MagNet (MagNet, Infolytica, Inc.) and the result was analysed with respect to the position of the CNT in the microchannel.…”
Section: Theoretical Characterisation Of Cnt Self‐assemblymentioning
confidence: 99%
“…Microscopic electromagnets were used for the local control of nuclear spin in a quantum Hall device [4]. Electromagnets were also used for the manipulation of submicrometer-scale magnetic materials, such as atoms, cells and magnetic nanoparticles [5]- [7].…”
Section: Introductionmentioning
confidence: 99%